Analisis Kemampuan Berpikir Kritis dan Hambatan Belajar Siswa Kelas XI Materi Translasi - Azka, Fullu; Isnarto, Isnarto; Junaedi, Iwan; Zaenuri, Zaenuri; Walid, Walid (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2024)
This research aims to identify and analyze students' critical thinking skills and learning barriers in learning mathematics translation material. The concept of translation is fundamental for students who want to master geometric transformations. Students must understand the basics of translation because this understanding of translation will be needed at a higher level. However, many students still experience obstacles in understanding translation material. Students experience learning impediments because of the difference between the expected achievements of critical thinking skill indicators, interpretation, analysis, evaluation, and inference, and the actual results. This research uses a qualitative descriptive research methodology, utilizing data collection techniques such as interviews, observation, and documentation. Data analysis was conducted using descriptive methods with 30 class XI-1 students as participants. Triangulation was used in the data collection process, which involved using teacher and student interviews, administering diagnostic tests, and textbook analysis (document analysis). The research results show that the average percentage of students' critical thinking abilities from the four indicators is 41.665%. Ontogenic, didactic, and epistemological barriers cause the low critical thinking skills of class XI-1 in studying translation. The research results can be used as considerations for teachers in designing learning to improve critical thinking skills and reduce students' learning barriers in learning translational material.